Managing Ureterovaginal Fistulas following Obstetric and Gynecological Surgeries - Upadhyay, Amit Mani; Kunwar, Ashok; Shrestha, Sanjesh; Pradhan, Hema Kumari; Karki, Aruna; Dangal, Ganesh (Journal of Nepal Health Research Council, 2018)
Background: Iatrogenic ureteric injuries leading to fistula are rare but devastating complications of obstetric and gynecological surgeries. The aim of the study was to review the demography of ureterovaginal fistula (UVF) and its surgical outcome in Kathmandu Model Hospital. Methods: This is a review of 15 patients of ureterovaginal fistula who were referred to department of Obstetrics and Gynaecology of Kathmandu Model Hospital from Feb 2014 to Sept 2017. We reviewed the demography, causes and surgical outcome of ureterovaginal fistula (UVF). Ten patients who had complete blind end at the distal ureter, underwent Lich-Gregoir extravesical ureteroneocystostomy. In other five patients, guide wire was successfully negotiated beyond the fistula site, however retrograde double J stenting could be done in only four patients. Results: All the patients had distal ureteric injury close to vesicoureteric junction leading to ureterovaginal fistula. Among them, majority were due to post-hysterectomy in 60% (n=9) followed by obstetrical procedures in 40% (n=6). Fourteen patients (93%) had successful closure of the fistula with complete preservation of renal function. Retrograde double J stenting was possible in patients who were referred earlier within two weeks of the onset of injury. Conclusions: Iatrogenic injury to the distal ureter during surgery was the leading cause for the ureterovaginal fistula. Endoscopic management with ureteric stents was still possible if the patients were referred earlier following primary surgery.